Characterization of moderate tendinopathy in ex vivo stress-deprived rat tail tendons - Leila Jafari; Martin Savard; Fernand Gobeil; Eve Langelier (BioMedical Engineering OnLine, 2019)
Abstract Background Stress deprivation (SD) has frequently been used as a model to study tendinopathy. Most of these studies have investigated either short-term (early tendinopathy) or long-term SD (advanced tendinopathy), while the transient mid-term SD has been given less attention. Therefore, the main objective of this study was to characterize mid-term SD. Methods To this end, live, healthy rat tail tendons (RTTs) were harvested and cultured without mechanical stress and then were divided into five groups based on their culture time (fresh, 2-day SD, 4-day SD, 6-day SD, and 10-day SD). For each group, the tendons were subjected to traction testing and pathohistology, immunohistochemistry, and viability assays. Results Our results showed that 4 days of SD resulted in moderate pathological changes in RTTs. These changes included increases in the space area between fibers, cell density, and fiber tortuosity as well as a decrease in collagen density and elongation of cell nuclei. No changes in the stress at failure of tendons were observed at this time point. Conclusions This simple ex vivo model is expected to be useful for studying the progression of tendinopathy as well as for testing potential mechanobiological or pharmacological therapy strategies to stop or reverse the progression of the pathology.